Frühe Strafverteidigung und Untersuchungshaft eine empirische Studie - Busse, Ulrike (Universitätsverlag Göttingen, 2008)
Can early criminal defense helping to avoid or shorten detention? When early criminal defense means to avoid unnecessary detention which burdens both the involved parties, the enforcement and detention and in terms of costs, the state in unnecessary ways? These questions are discussed in the present investigation. It represents the concept and the results of the accompanying scientific research from a 1998 pilot project carried out in the JVA Hannover. It relies on the analysis of over 1,300 criminal acts and the Federal Central Register's (Bundeszentralregister) statements, the evaluation of the detention list of the local court of Hanover and on extensive interviews with people involved in the project (defence lawyers, prosecutors, judges, court clerks and remand prisoners). The empirical findings of the accompanying be embedded in a legal framework and criminological conclusions are presented.